Association between C-reactive protein and metabolic syndrome in the Peruvian population of the PERU MIGRANT study - Vera-Ponce, Víctor Juan (2020)
Introduction: Metabolic syndrome (MetS) is a group of cardiovascular risk factors characterized by the presence of low-grade chronic inflammation. Among all the inflammatory biomarkers associated with MetS, the best characterized and well standardized is C-Reactive protein (CRP). Objectives: To evaluate the association between C-Reactive protein and metabolic syndrome in the Peruvian population of the PERU MIGRANT study. Methods: Secondary database analysis of the PERU MIGRANT study. MetS was considered according to the Harmonizing the Metabolic Syndrome criteria. For CRP, a cutoff point of ≥ 3 mg/L was established. Results: We worked with a total of 958 subjects. The prevalence of MetS was 24.53%. In the simple regression analysis, it was found that people with high CRP levels had a 75% higher frequency of having MetS, compared to those who did not present high CRP levels (PR = 2.21, 95% CI: 1.40 - 2.18). In multiple regression, it was observed that patients with high CRP levels had a 31% greater frequency of having MetS, compared to those with normal CRP levels; adjusting for the rest of the covariates (PR = 1.31, 95% CI: 1.05 - 1.62). Conclusions: Plasma CRP was positively associated with MetS. This suggests that a low-grade inflammatory process may be related to the presence of MetS. Against this, physicians should pay attention to glucose, lipid profile, and central obesity in patients with elevated plasma CRP levels.